Media Dan Metode untuk Percepatan Adopsi Teknologi Jagung Hibrida Spesifik Lokasi di Kabupaten Konawe Selatan Sulawesi Tenggara - Iskandar, Iskandar (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2011)
The aim of this research was an effective communication method to accelerate the adoption of hybrid maize technology in Southeast Sulawesi. This research used participation sixty farmers. The area selection was according to the purposive approach to hybrid maize farmers. The research sample was randomly chosen from two farmer groups: beginner and experienced farmers. The research design used experimental quasi, and data analysis used the qualitative description. Pre and post-test analysis on farmer groups on method and media resulted in effective value (EP) of demonstration method of 79.81%, video training of 63.13%, folder media of 47.09%. Covariant analysis of the above three methods resulted in an F value of 8.22. This meant there was variation among the three methods, with a probability of 99%. This also meant that the area-specific communication method was the appropriate participatory interactive communication methods. This model is effective to be applied because this communication model is based on communication sources and receivers’ needs.